The Role of Liver Transplantation for Liver Metastasis from Colorectal Cancer - Tomiyama, Koji; Dokus, M. Katherine; Errigo, Jennie; Laryea, Marie; Hernandez-Alejandro, Roberto (Digestive Disease Interventions, 2020)
As chemotherapy for colorectal cancer becomes effective for extending long-term survival, its liver metastases (colorectal cancer liver metastases [CRCLM]) are considered as the progression that best defines patient survival. Surgical resection is the most effective and only curative treatment for CRCLM. Although advancement in liver surgery to increase resectability of CRCLM has borne fruit, there are still limitations, namely tumor burden, remnant liver volume, and chemotherapy-related liver damage. CRCLM used to be considered a contraindication for liver transplantation (LTx) based on preliminary experience in the early era of LTx. Recent advancement in chemotherapy and surgical resection for CRCLM as well as improved outcome of LTx have attracted interest in revisiting this old dogma of LTx for CRCLM. Preliminary experience from Norway has shown promising results and potential for long-term survival with LTx. In this article, we review the history of LTx for CRCLM, rationale for revisiting the concept, early experience from Norway and discuss the issues around and future perspectives on LTx for CRCLM.
Keywords: colorectal cancer; liver metastases; liver transplantation